Effect of Suspension Freeze-concentration Technology on the Quality of Wine - Zhang, Q.; Sun, X.; Sheng, Q.; Chen, J.; Huang, W.; Zhan, J. (South African Journal of Enology and Viticulture, 2016)
One of the factors that inhibits the development of the Chinese wine industry is that the sugar content of the grape feedstock is insufficient. In order to produce wine with better qualities using these materials, concentrating the grape juice could be a good alternative to adding sugars. In this study, suspension freezeconcentration technology was applied to concentrating grape juice with a low sugar content. The freezeconcentrated grape juice was made into red and white wines separately. In the control group, red and white wines were made from chaptalized (sugar-enriched) grape juice. The physical and chemical indexes, sensory evaluation results and polyphenolic content of the wine were analysed to evaluate the practicality of applying the freeze-concentration technology in the wine industry. The results show that, after removing ice every 30 min for approximately 14 h with a -18°C coolant, grape juice with an initial sugar content of 14°Brix reached 23°Brix. Both the red wines and white wines made from freeze-concentrated grape juice were of a higher quality than the wines made from chaptalised grape juice. Moreover, the phenolic content was concentrated, which may provide health benefits. Thus, suspension freeze-concentration technology is a promising alternative to traditional chaptalisation technology.